FAMILY’S ROLE IN THE FORMATION OF THE DEVIANT BEHAVIOR OF A CHILD - Muranenko, Kateryna (PSYCHOLOGICAL JOURNAL, 2019)
The article presents the analysis of family’s role in child deviant behavior formation. The author describes the main functions of the family: reproductive, which consists in birth of children, the continuation of the genus; educational – the transfer of values, norms and rules of society, which influence on the formation of the personality of the child; economic-household (or economic), which is to provide all the material goods necessary for existence, to organize the food, to make improvements to the dwelling, to form and spend the family budget, etc.; recreational – the function of leisure organization, the formation of the culture of each member of the family; he function of social control – lies in the responsibility of the family for the behavior of its members in society in accordance with social norms and values; regenerative (or socio-status), which is related to the imposition of status, name, property, social status; psychotherapeutic function or function of emotional support aimed at psychological protection of every member of the family, his emotional stabilization; the function of sexual regulation, through which the society regulates the natural sexual needs of people, arranged in the form of marital relationships.There are individual, pedagogical, psychological and social deviant behavior factors. These factors are connected with family functions. Social factor of deviant behavior reflects in disruption of household family function. Pedagogical deviant behavior factor manifests it self in problems of educational, recreational, social control family functions. Psychotherapeutic family function must provide psychological comfort for every family member. Failure to fulfill this function is manifested in psychological deviant behavior factor. The failure of some functions in a family and education in dysfunctional family is a base of deviant behavior. The connection between family education and deviant behavior is confirmed by scientific researches. The failure of family structure is one of the main factors of predisposition to child’s deviant behavior. The author says that emotional contact between child and parents, parents’ attention and love to children, spending free time in a common kinds of activities are important for child’s personality development. The article also presents family as socialization institute in which child assimilates social norms, values, behavioral rules. It shows the results of questioning of schoolchildren and analysis of some aspects of modern family relationships. In conclusion, family can help child in adaptation and self-realization in society. At the same time family can create conditions for deviant behavior because of communication problems, less of psychological contact and absence of conditions of harmony development and education. So the system of child deviation prevention must pay attention not only to law, social and pedagogical aspects but to work with families. It is necessary to form conscious parenting of youth, to increasing of parents’ psychological culture level, giving to parents information about children education, family conflicts prevention etc.